Integration Augmented Reality-Based Game-Based Learning through the SAMR Model in Elementary Literacy and Problem-Solving Instruction - Herisa Hardiyanti Sholeha; Onwardono Rit Riyanto; Anasya Putri Febgiyo; Nonih Nur Syah Lukiyah (Journal of General Education and Humanities, 2026)
This study aims to make learning more engaging and interactive for students by integrating AR-supported game-based learning into the SAMR model. The integration of Augmented Reality (AR)-supported Game-Based Learning (GBL) using the SAMR model in Cirebon Regency. The study employed a quantitative descriptive approach supported by classroom observations, literacy and problem-solving tests, and teacher interviews. The participants were 168 elementary school students from schools implementing GBL–AR–SAMR learning and comparison classes alongside more conventional learning approaches. Data were analyzed using descriptive statistics and independent two-sample t-tests. The results showed that students participating in GBL–AR–SAMR learning achieved higher literacy and problem-solving outcomes than students in comparison classes. The average literacy score increased from 58.3 before implementation to 79.20 after implementation, while the average problem-solving score increased from 52.0 to 77.00. The independent two-sample t-test indicated a statistically significant difference between the two groups (p < 0.05). The integration of the SAMR model allowed teachers to shift from merely replacing media to redefining the learning experience. This article offers a unique perspective by developing AR-based learning practices within the local context of Cirebon, with implications for digital literacy, creativity, and students’ readiness to face the challenges of the digital age.